1975
DOI: 10.1677/joe.0.0660079
|View full text |Cite
|
Sign up to set email alerts
|

Androgenization: Alterations in the Mechanism of Oestrogen Action

Abstract: Total nuclear uptake of oestradiol, specific nuclear binding of oestradiol and oestrogen-induced proteins were studied in the uterus of femal Sprague-Dawley rats injected on postnatal day 3 with sesame oil or with 1-25 mg of testosterone propionate in sesame oil (androgenization). Total uptake of radioactivity was lower than normal in nuclei from uterine homogenates of androgenized females but was increased by the addition of excess cytosol from normal uterus. These data suggest that androgenization increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
2
9
0
2
Order By: Relevance
“…Previous studies demonstrated that exposure of experimental female rodents to androgens such as testosterone propionate (TP) at doses of 1.25 mg/d during the neonatal age produced permanent morphological, biochemical, and functional alterations in several organs and systems (Lobl, 1975;Schwartz et al, 1986;Carter et al, 1988). Treatment of rodents with high doses of androgens ranging from 1 to 25 mg/kg during prenatal or early postnatal periods induced changes in normal development of fetal genitalia, in uterine physiology, in hormonal homeostasis, and in sexual differentiation (Lobl and Maenza, 1975;Arriaza et al, 1988Wolf et al, 2002Hotchkiss et al, 2007a).…”
mentioning
confidence: 99%
“…Previous studies demonstrated that exposure of experimental female rodents to androgens such as testosterone propionate (TP) at doses of 1.25 mg/d during the neonatal age produced permanent morphological, biochemical, and functional alterations in several organs and systems (Lobl, 1975;Schwartz et al, 1986;Carter et al, 1988). Treatment of rodents with high doses of androgens ranging from 1 to 25 mg/kg during prenatal or early postnatal periods induced changes in normal development of fetal genitalia, in uterine physiology, in hormonal homeostasis, and in sexual differentiation (Lobl and Maenza, 1975;Arriaza et al, 1988Wolf et al, 2002Hotchkiss et al, 2007a).…”
mentioning
confidence: 99%
“…In this connection, several workers have reported that the uptake in vivo of tritiated estradiol by the uterus is significantly decreased in neonatally androgenized rats (Flerko et al, 1969;Tuohimaa and Johansson, 1971;Vertes and King, 1971;Maurer and Woolley 1971, 1974. However, there are only a few reports concerning changes in concentrations of estrogen receptors under these conditions (Lobl, 1975;Cidlowski and Muldoon, 1976;Gellert et al, 1977). Furthermore, it is unclear whether the reduction of uterine response to estrogen in persistent estrous rats is due to an altered hormonal environment induced by the neonatal treatment with steroids (Maurer and Woolley, 1975;Cidlowski and Muldoon, 1976) or to the direct action of the neonatally adminstered steroids on the immature rat uterus (Gellert et al, 1977).…”
mentioning
confidence: 99%
“…Although Gellert et al () did not find any significant effect on uterine response to estrogen after neonatal androgen exposure in prepubertal rats, others have reported a decrease in this responsiveness (Lobl, ; Lobl and Maenza, ; Campbell, ; Schwartz et al, ; Campbell and Modlin, ). Such discording results may be because androgenization exerts different effects according to the stage of development in which fetuses or neonatal animals are exposed (Lobl and Gorski, ; MacLusky and Naftolin, ; Arriaza et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…Early postnatal exposure to androgens may lead to adverse reproductive effects in the adulthood as dysfunctional steroidogenesis, irregularity on estrus cycle, and follicular growth impairment (Ongaro et al, ). Besides, in steroid target tissues, the presence of androgens during critical periods of sexual differentiation induces permanent alterations that may affect the responsiveness of these tissues to estrogen (Lobl et al, ; Lobl, ). There are some studies showing that androgen exposure can decrease the uterine response to estrogenic stimulation (Harris and Levine, ; Petrusz and Flerkó, ) and induce changes in the hormone‐induced uterine growth (Lobl and Maenza, ).…”
Section: Introductionmentioning
confidence: 99%